A LESS-CONSTRAINED (2,0) SUPER-YANG-MILLS MODEL THE COUPLING TO NON-LINEAR σ-MODELS - ALMEIDA, C.A.S. ALMEIDA; Chauca, J.; Doria, R.M. (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Considering a class of (2,0) super-Yang-Mills multiplets characterised by the appearance of a pair of independent gauge potentials, we present here their coupling to non-linear σ-models in (2,0)-superspace. Contrary to the case of the coupling to (2,0) matter superfields, the extra gauge potential present in the Yang-Mills sector does not decouple from the theory in the case one gauges isometry groups of σ-models.Considering a class of (2,0) super-Yang-Mills multiplets characterized by the appearance of a pair of independent gauge potentials, we present here their coupling to non-linear σ-models in (2,0)-superspace. Contrary to the case of the coupling to (2,0) matter superfields, the extra gauge potential present in the Yang-Mills sector does not decouple from the theory in the case one gauges isometry groups of σ-models.